Raising Awareness and Knowledge of Rural Communities against Lottery Fraud and Illegal Online Loans through Telephone and Short Message Services - Bashir, Abdul; Azwardi, Azwardi; Soebyakto, Bambang Bemby; Atiyatna, Dirta Pratama; Hamidi, Ichsan; Hamira, Hamira; Dwi, Rosada Sintya (Sricommerce: Journal of Sriwijaya Community Services, 2022)
The Covid-19 pandemic has had a major socio-economic impact on the community, especially the decline in income and job losses. The urgency of economic needs makes people make online loans that are illegal and have very high interest rates. The lack of public knowledge about licensed and illegal online loans has resulted in debtors being trapped in large debts and spreading personal data. Considering that rural communities who have low levels of education and knowledge are victims of prize draw scams which are disseminated via short message service (SMS) and telephone calls. Therefore, there is a need for socialization about illegal online loans and prize draw fraud to the community, especially village communities. The purpose of this service activity is to increase public awareness and knowledge about the legality of online loan services and prize draw fraud. After this service was carried out, the community in Kerinjing Village had knowledge about the legality of online loans, prevention and overcoming of online loans as well as vigilance against prize draw fraud via SMS and telephone. After the community service activities were carried out, it was found that 100% of the community understood illegal online borrowing and raffle prizes via telephone and SMS.